The more you judge the worse you feel. A judgemental attitude towards one's inner experience predicts depression and anxiety. (1st February 2019) - Barcaccia, Barbara; Baiocco, Roberto; Pozza, Andrea; Pallini, Susanna; Mancini, Francesco; Salvati, Marco
Abstract: Literature reviews have shown that trait-mindfulness is significantly correlated to emotional wellbeing, both in adults and in children. Particularly, being judgemental towards one's inner thoughts, feelings and sensations, and acting unawares, is associated with higher maladjustment. In the present cross-sectional study, we explored the role of the different facets of mindfulness in both anxiety and depression, controlling for the effects of gender, age, rumination, and worry, and analysed which facets of mindfulness have the strongest effect in predicting depression and anxiety. Two-hundred seventy-four community adults were assessed in the domains of depression, anxiety, rumination, worry, and mindfulness. Regression analyses showed that, among the facets of mindfulness, a judgemental attitude towards one's thoughts and feelings is the strongest predictor of both depression and anxiety. Our study highlights the importance of a normalising, accepting, non-judgemental attitude to decrease anxiety and depression, and to foster wellbeing.